Immunological Feature and Transcriptional Signaling of Ly6C Monocyte Subsets From Transcriptome Analysis in Control and Hyperhomocysteinemic Mice - Yang, Pingping; Liu, Lu; Sun, Lizhe; Fang, Pu; Snyder, Nathaniel; Saredy, Jason; Ji, Yong; Shen, Wen; Qin, Xuebin; Wu, Qinghua; Yang, Xiaofeng; Wang, Hong (Frontiers in Immunology, 2021)
Background: Murine monocytes (MC) are classified into Ly6Chigh and Ly6Clow MC. Ly6Chigh MC is the pro-inflammatory subset and the counterpart of human CD14++CD16+ intermediate MC which contributes to systemic and tissue inflammation in various metabolic disorders, including hyperhomocysteinemia (HHcy). This study aims to explore molecule signaling mediating MC subset differentiation in HHcy and control mice. Methods: RNA-seq was performed in blood Ly6Chigh and Ly6Clow MC sorted by flow cytometry from control and HHcy cystathionine β-synthase gene-deficient (Cbs-/-) mice. Transcriptome data were analyzed by comparing Ly6Chigh vs Ly6Clow in control mice, Ly6Chigh vs Ly6Clow in Cbs-/- mice, Cbs-/- Ly6Chigh vs control Ly6Chigh MC and Cbs-/- Ly6Clow vs control Ly6Clow MC by using intensive bioinformatic strategies. Significantly differentially expressed (SDE) immunological genes and transcription factor (TF) were selected for functional pathways and transcriptional signaling identification. Results: A total of 7928 SDE genes and 46 canonical pathways derived from it were identified. Ly6Chigh MC exhibited activated neutrophil degranulation, lysosome, cytokine production/receptor interaction and myeloid cell activation pathways, and Ly6Clow MC presented features of lymphocyte immunity pathways in both mice. Twenty-four potential transcriptional regulatory pathways were identified based on SDE TFs matched with their corresponding SDE immunological genes. Ly6Chigh MC presented downregulated co-stimulatory receptors (CD2, GITR and TIM1) which direct immune cell proliferation, and upregulated co-stimulatory ligands (LIGHT and SEMA4A) which trigger antigen priming and differentiation. Ly6Chigh MC expressed higher levels of MΦ markers, whereas, Ly6Clow MC highly expressed lymphocyte markers in both mice. HHcy in Cbs-/- mice reinforced inflammatory features in Ly6Chigh MC by upregulating inflammatory TFs (Ets1 and Tbx21) and strengthened lymphocytes functional adaptation in Ly6Clow MC by increased expression of CD3, DR3, ICOS and Fos. Finally, we established 3 groups of transcriptional models to describe Ly6Chigh to Ly6Clow MC subset differentiation, immune checkpoint regulation, Ly6Chigh MC to MΦ subset differentiation and Ly6Clow MC to lymphocyte functional adaptation. Conclusions: Ly6Chigh MC displayed enriched inflammatory pathways and favored to be differentiated into MΦ. Ly6Clow MC manifested activated T-cell signaling pathways and potentially can adapt the function of lymphocytes. HHcy reinforced inflammatory features in Ly6Chigh MC and strengthened lymphocytes functional adaptation in Ly6Clow MC.